Patience Education as an Implementation of Moral Education Toward the Self - Jamaludin, Jamaludin; Ghofur, Abdul; Romlah Abu Bakar Askar, Romlah Abu Bakar Askar (Al-Ulum: Jurnal Pendidikan Islam, 2025)
Education is a planned effort to create a learning atmosphere and educational process that enables students to actively develop their potential. Education serves as the primary foundation in shaping human personalities free from ignorance. In the educational process, patience plays a vital role as it is needed in every stage of developing good character. This patient attitude can influence the quality of education one receives. Based on this, this research aims to analyze the relationship between patience and educational values that grow within individuals, as reflected through their attitudes and speech. These values are the result of efforts made in achieving educational goals. Pacient is one of the outcomes of moral education directed at oneself, reflecting natural human behavior or disposition that requires proper guidance.